PENGARUH ELEMEN JASA TERHADAP KEPUASAN KONSUMEN DAN NIAT UNTUK SETIA ATAU BERGANTI PENYEDIA JASA - Euis Eka Pramiarsih (Jurnal Bisnis dan Kewirausahaan, 2015)
Service quality is not quality of what is delivered (core quality). However , the quality of how the service is delivered (relational quality) can be put into service quality dimensions. Other respect that could be considered by costumers to make a decision to choose which service that they would use was perceived value. Costumers always compare what they had to pay with what they received. And it could impact to behavioral intentions. this research investigated the relationship between three elements-core service quality, relational service quality and perceived value –and customer satisfaction and future intentions in service industry . Using structural equation modeling, result of this research revealed that three service elements were important drivers of customer satisfaction further, show that perceived value was the most important driver of customer satisfaction, and relational quality was more important driver of customer satisfaction than core quality. It related with a kind of the service that was used in this research , high contact service. Beside that, a direct link between customer satisfaction and future intentions was established . A major conclusion was that both perceived value and service quality dimensions should be incorporated into customer satisfaction models to provide a more complete picture of drivers of satisfaction.